Comparison the Efficiency of Ir doped-TiO2 Nanostructure as Risk-Reduction Materials for Toluene and n-Hexane - Ho, Van Thi Thanh; Chau, Dung Hung; Nguyen, Ngan Thi Thanh; Huy, Khang Le (International Journal of Advanced Engineering Research and Science, 2022)
We have studied comparison the efficiency of Ir doped-TiO2 nanostructure as risk-reduction materials for toluene and n-hexane. In particular, the most attractive advantages of our Ir doped-TiO2 may be a high efficiency of VOCs treatment as well as the different mechanism of Ir doped-TiO2 Risk-Reduction Materials between n-hexane and toluene organic compounds treatment have been studied in work. The study results show that there is a significant difference in the maximum achievable efficiency of toluene and n-hexane organic compounds degradation using Ir-TiO2 photocatalyst. The photocatalytic material has the highest toluene treatment efficiency at 97.50 % which is much higher than that for n-hexane compound (60.03%). This outcome may be due to the difference in the structure of these two organic compounds. According to the scheme proposed by Montelio's research group [63], the alkane, after meeting the free hydroxyl radical OH∙, will be cleaved into alkyl radicals; the OH∙ radicals are essentially electrophilic. In the case of alkanes, they will attack the stable cationic carbon-forming site on the secondary carbons. Due to the conjugation effect of the aromatic ring and the methyl radical in the toluene, the H of the ring will become flexible; therefore, toluene will be more easily decomposed.